Experimental modification of the internal solitary wave force exerted on a horizontal transverse cylinder due to wave-flow and vortex shedding. (1st February 2023) - Wang, Shaodong; Du, Hui; Wei, Gang; Peng, Pai; Xuan, Pu
Abstract: Based on the experimental measurements of the ISW force on a horizontal transverse cylinder in a gravitationally stratified fluid flume, the modification formulas of the empirical coefficients in the ISW force calculations are proposed by use of parameter optimization methods such as the least square method and wavelet transform. The time series and spatial characteristics of various forces exerted on a horizontal transverse cylinder by an ISW, including the wave force, the reduced gravity and the vortex shedding force, were obtained, and their description precision was improved. It is shown that those forces exerted on a horizontal transverse cylinder involve the empirical coefficients, including the inertial force coefficient C m and the drag force coefficient C d in the Morison formula, and the vortex shedding lift coefficient C l in virtue of the vortex shedding frequency ω s, in which the fitting modification formulae of the empirical coefficients and vortex shedding frequency with the Reynolds number R e (1000–3000) by use of experimental data are approximated to the exponential function and the polynomial function, respectively. The calculation accuracy of the ISW force with modified coefficients is significantly improved compared with those forces having constant coefficients, in which the average relative errors of the horizontal force and the vertical vortex shedding lift with modifications are reduced by approximately 71% and 46%, respectively. In addition, some characteristic descriptions closer to the actual processes are obtained, including the time series variation of various forces, its contribution to the horizontal pushing or pulling force, and to the vertical downward drag or the 'double peak' force, and to its spatial variation with varying cylinder submerged depth, which further improves the understanding of the temporal and spatial features of the ISW acting on structural objects. Highlights: The ISW force on a horizontal transverse cylinder is measured experimentally. The modification formulas of the empirical coefficients in the ISW force calculations are proposed. The time series and spatial characteristics of various forces exerted on a horizontal transverse cylinder by an ISW are given.